Utilization of the Discovery Learning Model to Overcome Islamic Cultural History Learning Problems in Madrasa - Imam Tabroni; Susana Susana; Agil Mulyadi; Novie Zaelani (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
Islamic cultural history (SKI, Sejarah Kebudayaan Islam) is part of the Islamic religious education curriculum. In madrasa, this subject became a particular subject. Similar to another history subject, this subject has many general problems in practice. This paper aimed to determine the utilization of the Discovery Learning model in SKI learning at Islamic Junior High School (MTs) YAKPI Kalijati Subang, West Java Province. This study applied qualitative research with a qualitative descriptive type. Interviews, observations, and documentation were data collection methods to achieve the study objectives. The study found that utilization of the discovery learning model contributed to overcoming the SKI learning problems. The main problem included many aspects that related to achieving the learning objectives. This study also indicates that the teacher needed to combine the discovery learning model with digital-based learning media and outdoor-based learning methods.